Gap analysis of climate adaptation policymaking in Coastal Virginia - Eghdami, Sadegh; Michel, Valerie; Shafiee-Jood, Majid; Louis, Garrick (Frontiers in Climate, 2023)
Due to its inherent multidimensionality and complexities, successful climate adaptation policymaking requires a concerted effort among multiple governance levels. Discovering the challenges and governance gaps can provide insights for policymakers paving the way for more effective policies in the future. This paper intends to provide such analysis for Coastal Virginia, a strategic region in the United States receiving significant climate impacts, particularly sea-level rise (SLR) and flooding. Utilizing semi-structured interviews with the main stakeholders and building on the adaptation framework of Moser and Ekstrom, we identify, categorize, and relate main adaptation challenges to better understand the gaps and underlying institutional dynamics causing them. Intergovernmental coordination and comprehensive planning and prioritization are the main overarching challenges, with high emphasis in the literature, while the challenge of retreat and the private sector are less discussed. It is followed by recommendations for different levels of government, informing the path forward from the stakeholders' perspective. A discussion of findings provides several implications for local, state, and federal policymakers. This research could be extended to other coastal and non-coastal areas to help formulate national and sub-national adaptation policies that maintain a holistic vision for adaptation policymaking while pondering the context-specificities of states, regions, and localities. It would be an essential task as adapting to climate change is still in its infancy stages, with the prospect of staying with us for decades to come.